Applying Disability Theory in Technical Education: Toward Inclusive Curriculum and Infrastructure - Riyadi, Andrian; Adiningtyas, Ferina Suci; Perdana, Helmi Kusuma; Al Lathifah, Andini Fajari (The Center for Disability Studies and Services Brawijaya University, 2025)
The present study explores the application of disability theory in technical education, with a view to identifying the key barriers faced by students with disabilities and formulating inclusive strategies. The primary objective is to cultivate equitable and competency-aligned technical education through curriculum adaptation, assistive technology, and accessible infrastructure. Utilising a qualitative systematic literature review (SLR) approach, a comprehensive analysis of 48 peer-reviewed articles published between 2019 and 2024 was conducted. These articles were subjected to content analysis to extract thematic patterns related to structural, cultural, and technical barriers. The findings indicate that students with disabilities encounter constrained access to physical infrastructure, adverse social perceptions, and an absence of adaptive learning technologies. The study emphasises the importance of inclusive curriculum design and assistive tools such as screen readers and real-time transcription applications to enhance participation without compromising competency standards. The novelty of this study lies in its integrative synthesis of disability theory into technical education, offering a strategic framework that bridges inclusive pedagogy, infrastructure reform, and technological innovation. These insights contribute to the development of more inclusive technical education, especially in under-researched regional contexts.